KEBIASAAN JAJAN SISWA SEKOLAH DASAR (Studi Kasus di SDN Lawanggintung 01 Kota Bogor) - Yunita Syafitri; Hidayat Syarief; Yayuk Farida Baliwati (Food and Nutrition Society of Indonesia, 2009)
Healthy foods contribute to elementary school student proper growth and development. During school time they have greater access and sufficient opportunity to consume street food that available at school. However, poor street food choices can result in unbalance diet. Availability of street food in school play significant role to elementary school student diet. Street food can contribute 10-20% nutrients toward student daily consumptions. Street food devide into main dishes, snacks, and beverages. The aim of this study was to assess snacking habit of elementary school student in SDN Lawanggintung 01 Kota Bogor. Snacking habits devined as number of street food type and frequency of snacking in school area included canteen merchants and outside school permanent merchants. Design of this study was cross sectional. Fifty student were selected using simple random sampling. Street food contributed to 26.0% energy; 18.7% protein; 22.9% lipid, 20.0% iron; 19.1% vitamin A; dan 24.8% vitamin C to total daily intake. Street food had contribute to 23.0% energy; 21.7% protein; 30.9% lipid, 19.5% iron; 24.1% vitamin A; dan 26.6% vitamin C to adequate intake level. Age and gender had not related to street food habits. Pocket money to purchased food is related to street food habits. Childrens familiy social economic characteristic not related to street food habits. Pocket money to purchased food affected street food habits.